10x-9y+13=0

Simple and best practice solution for 10x-9y+13=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-9y+13=0 equation:


Simplifying
10x + -9y + 13 = 0

Reorder the terms:
13 + 10x + -9y = 0

Solving
13 + 10x + -9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + 10x + -13 + -9y = 0 + -13

Reorder the terms:
13 + -13 + 10x + -9y = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 10x + -9y = 0 + -13
10x + -9y = 0 + -13

Combine like terms: 0 + -13 = -13
10x + -9y = -13

Add '9y' to each side of the equation.
10x + -9y + 9y = -13 + 9y

Combine like terms: -9y + 9y = 0
10x + 0 = -13 + 9y
10x = -13 + 9y

Divide each side by '10'.
x = -1.3 + 0.9y

Simplifying
x = -1.3 + 0.9y

See similar equations:

| 4m+2=30 | | 5(8-6x)=-7x+2(-8x-8) | | -0.1x-5x=-18.87 | | 12m-10= | | -x+1=-7x+1 | | a+22=52 | | 5x+26+3x+60=180 | | 4x+2y+0.25z=100 | | 0+y=0 | | 5x+26=3x+60 | | 0.833+2.5x=-6.5+0.66 | | 5x-8y=64 | | 10-4z=22-6z | | 18-3t=6 | | 4(1+2a)=-6a(a-3) | | 5y-3=7y | | 7+4n=23 | | 4x-3=2x+38 | | 220+220(0.105)-220(0.1)=x | | 5+5x-6=9 | | 8xn=51 | | 2x*5=4x+13 | | 4(-3k+8)=-6k+2(5k+8) | | Ix-4I=-3 | | 3n+6=16 | | F(x)=cos(pi+x) | | 3y+2=7y+10 | | g(z)=Cos(pi+g) | | 4y+2x=13.50 | | .77=In(y) | | 46=-5(m+3)-7(m-7) | | 0.77=ln(y) |

Equations solver categories